EXTRAVERSION/INTROVERSION AND AGE-RELATED DIFFERENCES IN SPEED-ACCURACY TRADEOFF - Meira Jr, Cassio de Miranda; Moraes, Renato; Moura, Mariana; Ávila, Luciana Toaldo Gentilini; Tosini, Laura; Magalhães, Fernando Henrique (Revista brasileira de medicina do esporte, 2018)
ABSTRACT Introduction: Extraversion/introversion and age differences might influence speed-accuracy tradeoff. Objective: The speed-accuracy tradeoff was investigated in extroverted and introverted female children, young adults and older adults. Method: Participants carried out an alternative version of Fitts’ task, which involved making alternate clicks with the mouse held in the dominant hand, moving as fast as possible, on two rectangular targets on a computer screen in order to make twelve attempts at six random levels of difficulty (twelve combinations of target widths and distances between targets). Each of the three groups was composed of 16 introverted and 16 extroverted subjects, based upon Brazilian versions of Eysenck’s questionnaire. Results: Elderly introverts fell short of the target more often and committed more overall errors than the elderly extroverts. Additionally, compared to their younger adult counterparts, the elderly subjects fell short of the target more often and committed more overall errors, besides taking longer to complete the task with higher levels of difficulty. Conclusion: The findings were interpreted in light of theories designed to explain the main processes underlying extroversion/introversion and age-related differences. Level of Evidence II; Lesser quality prospective study. RESUMEN Introducción: Las diferencias de extroversión/introversión y edad pueden influir en el cambio velocidad-precisión. Objetivo: El cambio velocidad-precisión fue investigado en mujeres jóvenes adultas y de la tercera edad introvertidas y extrovertidas. Método: Las participantes realizaron una versión alternativa de la tarea de Fitts, que consistía en hacer clic alternadamente con el ratón, usando la mano dominante, lo más rápidamente posible, en dos objetos rectangulares en la pantalla de la computadora, a fin de realizar doce tentativas con seis niveles aleatorios de dificultad (doce combinaciones de anchos y distancias entre los objetos). Cada uno de los tres grupos fue compuesto por 16 introvertidas y 16 extrovertidas, con base en las versiones brasileñas del cuestionario de Eysenck. Resultados: Las mujeres de tercera edad introvertidas acertaron menos el objeto con más frecuencia y cometieron más errores generales en comparación a las mujeres de tercera edad extrovertidas. Además, las mujeres de tercera edad acertaron menos el objeto con más frecuencia y cometieron más errores generales, además de demorar más tiempo para concluir las tareas con niveles mayores de dificultad cuando comparadas con las mujeres jóvenes adultas. Conclusión: Los hallazgos fueron interpretados con base en las teorías creadas para explicar los principales procesos sobre las diferencias relacionadas a la extroversión/la introversión y a la edad. Nivel de Evidencia II; Estudio prospectivo de menor calidad. RESUMO Introdução: Diferenças de extroversão/introversão e idade podem influenciar na troca velocidade-precisão. Objetivo: A troca velocidade-precisão foi investigada em garotas, jovens adultas e idosas extrovertidas e introvertidas. Método: As participantes realizaram uma versão alternativa da tarefa de Fitts, a qual consistia em clicar alternadamente com a mão dominante no mouse, o mais rápido possível, em dois alvos retangulares na tela do computador, a fim de fazer doze tentativas em seis níveis aleatórios de dificuldade (doze combinações de larguras e distâncias entre os alvos). Cada um dos três grupos era composto por 16 introvertidas e 16 extrovertidas, com base nas versões brasileiras do questionário de Eysenck. Resultados: As idosas introvertidas acertaram menos o alvo com mais frequência e cometeram mais erros gerais em comparação às idosas extrovertidas. Ainda, as idosas acertaram menos o alvo com mais frequência e cometeram mais erros gerais, além de demorarem mais tempo para concluírem as tarefas com níveis maiores de dificuldade quando comparadas com as jovens adultas. Conclusão: Os achados foram interpretados com base nas teorias criadas para explicarem os principais processos sobre as diferenças relacionadas à extroversão/introversão e à idade. Nível de Evidência II; Estudo prospectivo de menor qualidade.